Mechanistic insights into synergistic effects using coupled PK-PD modeling - Jinzhou Sun; Qianqian Chen; Chumeng Zhuang; Xiaohong Li; Li Yu; Weifeng Jin (Scientific Reports)
Abstract Develop a novel coupled PK-PD model and apply it to quantitatively evaluate the synergistic effects of Hydroxysafflor Yellow A (HSYA) combined with Calycosin (CA) in the treatment of ischemic stroke. A total of 6 rats were modelled for middle cerebral artery occlusion (MCAO). Plasma was collected from the submandibular venous plexus of rats after the administration of HSYA and CA, and was detected and analyzed by LC-MS method. The plasma expression levels of Caspase-9, IL-1β and SOD in rats were also determined by ELISA kit. Meanwhile, a coupled PK-PD model was proposed, incorporating interaction terms between drugs and coupling of pharmacodynamic effects, to quantitatively reveal their interactions. Moreover, a numerical solution technique based on optimization methods was proposed, enabling the model to be effectively applied to experimental data. Based on the coupled PK model, HSYA and CA significantly increased each other’s metabolic rates. The model also showed that CA had a larger apparent volume of distribution and clearance in rats, while HSYA had a shorter mean retention time and elimination half-life. The coupled PK-PD model indicated a synergistic effect between HSYA and CA on all three pharmacodynamic markers, with HSYA contributing more significantly. Despite individual variability among the six rats, the parameter interpretations remained consistent. The proposed coupled PK-PD model and its numerical solution algorithm successfully revealed the synergistic effects of HSYA and CA in the treatment of ischemic stroke. This model lays the foundation for future models with more complex interactions and effects.